(untitled) (The Journal of Plant Protection Sciences, 2022)
The experiment was carried out over two consecutive years to study the impact of incidence of foot rot of betelvine caused by Phytophthora parasitica and growth, yield, and keeping quality by applying two bioagents, viz., P. fluorescens and -1 Trichoderma harzianum. P. fluorescens inoculated in 500 kg oil cake ha was applied once at pre-monsoon, twice during -1 pre- and post- monsoon and four times at quarterly intervals. T. harzianum inoculated in 500 kg oil cake ha was applied at quarterly intervals. Bordeaux mixture (BM) was used to compare the treatments in preventing the intensity of foot rot. The results revealed that minimum foot rot disease occurred where four drenching and eight sprayings of BM at monthly st nd and fortnightly intervals respectively were applied in the 1 year. In the 2 year, the minimum foot rot disease was -1 recorded in the treatment where four applications of the Trichoderma preparation ha at quarterly intervals were given. The maximum foot rot disease was recorded in control treatment. The yield parameters like fresh weight of 100 leaves and st leaf yield were good in treatments where BM was applied. Trichoderma applications resulted in better c : b ratio during 1 year, where as applications of P. fluorescens over two year analysis of pooled data gave the best c : b ratio.